On the Role of Enthalpic and Entropic Contributions to the Conformational Free Energy Landscape of MIL‐101(Cr) Secondary Building Units. Issue 12 (15th September 2020) - Kollias, Loukas; Cantu, David C.; Glezakou, Vassiliki‐Alexandra; Rousseau, Roger; Salvalaglio, Matteo
Abstract: The thermo‐structural behavior of metal‐organic framework (MOF) precursors is responsible for regulating the introduction of defects in MOF structures during synthesis. In this paper, factors affecting the flexibility of MIL‐101(Cr) half‐secondary building units (half‐SBUs) are evaluated in solution using enhanced sampling methods. In particular, entropic and enthalpic contributions to the conformational free energy landscape of isolated MIL‐101(Cr) half‐SBUs are calculated in water, in the presence and absence of ionic species (Na + and F − ), and in N, N ‐dimethylformamide (DMF). This analysis leads to the observation that the interplay between enthalpy and entropy determines the most probable conformational state for half‐SBUs. This observation extends to the most relevant SBU intermediate, in which conformational entropy plays a key role in stabilizing configurations that differ from those found in the MIL‐101(Cr) crystal structure. The findings highlight the importance of explicitly considering entropic effects, associated with finite‐temperature sampling when estimating the relative stability of different conformers of SBUs. Abstract : The configurational free energy landscape of metal‐organic framework precursors is expressed in terms of entropically and enthalpically favored conformers. Changes in synthesis conditions and mixture composition appreciably affect the entropy and enthalpy profiles. Consequently, study of enthalpic and entropic contributions provides a mechanistic understanding of how certain conformers can be promoted or hindered during the early stages of assembly.